What Are the Experiences of People with COPD Using Activity Monitors?: A Qualitative Scoping Review. Issue 1 (31st December 2022) - Wilde, L. J.; Sewell, L.; Percy, C.; Ward, G.; Clark, C.
Abstract: Physical activity monitoring technology (e.g. smartphone apps or wearables) can objectively record physical activity levels, potentially support interventions to increase activity levels, and support the self-management of Chronic Obstructive Pulmonary Disease (COPD). Insight into patients' experiences of monitoring physical activity is needed to inform future healthcare practice and policy utilizing this technology to support long-term positive health behavior change. This scoping review aimed to explore the experiences of using technology for monitoring physical activity among people with COPD. The Joanna Briggs Institute scoping review methodological framework was used. Relevant scientific databases (CINAHL Complete, MEDLINE, PsycINFO, SPORTDiscus, Cochrane Library and Scopus) were searched from 1st January 2016 to 16th March 2021. Thematic synthesis was used to analyze the data. Twelve studies exploring the experiences of people with COPD using technology for monitoring physical activity were included in the synthesis. Seven themes were developed and summarize experiences: 1) Monitoring and keeping track of their activity and health, 2) Supporting motivation to be active, 3) Acceptability of the device, 4) Experiencing technical issues with the device, 5) Setting appropriate and achievable goals for their health condition, 6) Integrating the device into their life and daily routine, and 7) Perceived physical and psychological benefits of using the device. Further high-quality research is needed to understand the experiences of people with COPD using technology to monitor physical activity in everyday life and better self-manage their health condition. Supporting people with COPD to monitor their physical activity could enable them to better self-manage their health condition.